Preparation and evaluation of icariside II-loaded binary mixed micelles using Solutol HS15 and Pluronic F127 as carriers. (21st November 2016) - Hou, Jian; Wang, Jing; Sun, E.; Yang, Lei; Yan, Hong-Mei; Jia, Xiao-Bin; Zhang, Zhen-Hai
Abstract: An effective anti-cancer drug, icariside II (IS), has been used to treat a variety of cancers in vitro . However, its poor aqueous solubility and permeability lead to low oral bioavailability. The aim of this work was to use Solutol®HS15 and Pluronic F127 as surfactants to develop novel mixed micelles to enhance the oral bioavailability of IS by improving permeability and inhibiting efflux. The IS-loaded mixed micelles were prepared using the method of ethanol thin-film hydration. The physicochemical properties, dissolution property, oral bioavailability of the male SD rats, permeability and efflux of Caco-2 transport models, and gastrointestinal safety of the mixed micelles were evaluated. The optimized IS-loaded mixed micelles showed that at 4:1 ratio of Solutol®HS15 and Pluronic F127, the particle size was 12.88 nm with an acceptable polydispersity index of 0.172. Entrapment efficiency (94.6%) and drug loading (9.7%) contributed to the high solubility (11.7 mg/mL in water) of IS, which increased about 900-fold. The SF-IS mixed micelle release profile showed a better sustained release property than that of IS. In Caco-2 cell monolayer models, the efflux ratio dramatically decreased by 83.5%, and the relative bioavailability of the mixed micelles (AUC0–∞ ) compared with that of IS (AUC0–∞ ) was 317%, indicating potential for clinical application. In addition, a gastrointestinal safety assay also provided reliable clinical evidence for the safe use of this micelle.